Penguatan Kompetensi Guru Melalui Pembelajaran Ramah Anak Berbantuan Game Edukasi Digital untuk Pencegahan Bullying - Oktavianingsih, Eka; Fitroh, Siti Fadjryana; Tahir, Muhlis; Fatmawati, Fatmawati; Izzati, Masittha; Kiptiyah, Maryatul (Jurnal Pengabdian UNDIKMA, 2026)
This community service program aims to enhance teachers’ competencies in preventing bullying through child-friendly learning supported by the digital educational game “Jagoan Kebaikan.” The program employed mentoring and simulation methods and was conducted in partnership with TK Negeri Pembina Pejagan Bangkalan, involving 11 teachers as participants. Evaluation was carried out through pre-test and post-test assessments administered during the training activities to measure teachers’ knowledge and skills, with data analyzed using the Paired Sample t-Test. The results indicate a significant improvement in teachers’ knowledge and skills following the implementation of the program. Based on the post-test results, 6 participants (54.5%) demonstrated very good levels of knowledge, 4 participants (36.3%) showed good knowledge, and 1 participant (9%) was categorized as having a sufficient level of knowledge. These findings suggest that the mentoring activities were effective in enhancing teachers’ competencies in bullying prevention through child-friendly learning supported by digital educational games.